Efecto del zumo del fruto de Myrciaria dubia H.B.K McVaugh sobre la lipoperoxidación inducida en tejido hepático de Rattus norvegicus var. albinus con cáncer de colon - Aguilar Paredes, Diana Marysol (2018)
The objective of this work was to determine the effect of the fruit juice of Myrciaria dubia H.B.K McVaugh on the lipoperoxidation induced in the liver tissue of Rattus norvegicus var. albinus with colon cancer. We worked with 24 specimens grouped in 02 groups; group I (White) only received water, group II conformed by 18 rats with colon cancer and subdivided randomly into 03 subgroups: Control: rats with colon cancer, Problem (1) and Problem (2) were administered 50 mg / kg and 150 mg / kg. p.c of M. dubia respectively orally; each group consisted of 6 rats. To determine the effect of M. dubia on lipoperoxidation, the colorimetric method of substances reactive to thiobarbituric acid (TBARS) was used, using lipoperoxidation levels of malondialdehyde (MDA), at a length of 532 nm; using liver tissue as a sample. The mean levels of MDA for the target group was 0.794 nmol / g, control group was 3.166 nmol / g and problem groups (1 and 2) 2.280 and 1.849 nmol / g respectively. The results were statistically analyzed by performing the ANOVA; finding a significant difference (p <0.05) between the groups being confirmed with the Duncan test and the Tukey test. It is concluded that the administration of the fruit juice of Myciaria dubia H.B.K McVaugh decreases the levels of MDA, lipoperoxidation marker, in liver tissue of Rattus norvegicus var. albinus with colon cancer